2015
DOI: 10.1002/fam.2344
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of impregnation of ammonium polyphosphate fire retardant in poplar wood using microwave heating

Abstract: Summary Poplar samples were impregnated with ammonium polyphosphate fire retardant at various pressures and durations after they were pretreated with microwave heating. The effects of the pressure and duration on the flame‐retardation and smoke‐suppression properties were investigated with cone calorimeter analysis. The peak heat release rate (pk‐HRR), total heat release (THR), and total smoke product (TSP) of treated woods were measured for samples of pretreated and untreated with microwave. After the impregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…However, the obvious improvement in ignition time and the decrease in maximum HRR of densified wood at various heat fluxes confirm the effective fire retardancy of the dense and self‐formed char layer on the densified wood surface. The combustion performance between the densified wood without fire retardants and other flame‐retardant techniques further proved the superior fire retardancy of densified wood (Table S2, Supporting Information) …”
Section: Resultsmentioning
confidence: 85%
“…However, the obvious improvement in ignition time and the decrease in maximum HRR of densified wood at various heat fluxes confirm the effective fire retardancy of the dense and self‐formed char layer on the densified wood surface. The combustion performance between the densified wood without fire retardants and other flame‐retardant techniques further proved the superior fire retardancy of densified wood (Table S2, Supporting Information) …”
Section: Resultsmentioning
confidence: 85%
“…The flame retardant properties, such as peak heat release rate, total heat released and total smoke released, were measured for samples of pretreated and untreated with microwave and characterized by cone calorimeter. It was found that the treated wood showed better flame retardant properties, and moreover, the microwave pretreatment of wood can also increase the fire retardant properties of APP impregnated wood [61]. Wang et al found that the expanded vermiculite treatments improve the flame retardant properties of plywood.…”
Section: Coatings With Synergistic Flame Retardantsmentioning
confidence: 99%
“…With this technique, high weight gains of up to 100% can be obtained depending on the wood’s anatomy, the solution’s viscosity, and the molecular weight of the compounds in solution [ 36 , 37 , 38 , 39 ]. Impregnation using phosphorus-based compounds such as ammonium polyphosphate [ 40 ], guanyl urea phosphate [ 41 ] or organo-phosphorus compounds [ 42 ] provides an improvement of wood FR properties. However, it can be difficult and costly to impregnate timbers that have low permeability using this approach due to the need for non-continuous processes and drying time [ 43 ].…”
Section: Introductionmentioning
confidence: 99%